Ground defected planar super-wideband antenna: a suitable transceiver for short distance wireless communication - Azim, Rezaul; Siddique, A. K. M. Ariful Haque (Penerbit Universiti Kebangsaan Malaysia, 2018)
A planar microstrip patch super-wideband antenna is presented for short distance wireless communication applications. The antenna is comprised of a simple patch and a ground plane and etched on two sides of a 1.6 mm-thick standard FR4 substrate material with a relative permittivity of 4.5 and loss tangent (0.02). The proposed antenna possesses a compact size of 29 × 20.5 mm2 with an electrical dimension of 0.25 λ × 0.18 λ. To enhance the operating bandwidth, the ground plane is modified by adding seven small rectangular slots on its upper side. Through numerical studies, it is found that insertion of the slots enhances the coupling between the patch and ground plane resulting in achievement of a super-wide operating band. From the measurements, it is observed that the fabricated prototype antenna has a bandwidth from 2.63 to more than 18 GHz, a symmetric omnidirectional radiation characteristic and the maximum peak gain of 5.85 dBi which makes it a suitable transceiver for short distance communication applications.